SARS‐CoV‐2 S1 and N‐based serological assays reveal rapid seroconversion and induction of specifc antibody response in COVID‐19 patients (2020)
As the Coronavirus Disease 2019 (COVID-19), which is caused by the novel SARS-CoV-2, continues to spread rapidly around the world, there is a need for well validated serological assays that allow the detection of viral specifc antibody responses in COVID-19 patients or recovered individuals. In this study, we established and used multiple indirect Enzyme Linked Immunosorbent Assay (ELISA)-based serological assays to study the antibody response in COVID-19 patients. In order to validate the assays we determined the cut of values, sensitivity and specifcity of the assays using sera collected from pre-pandemic healthy controls, COVID-19 patients at diferent time points after disease-onset, and seropositive sera to other human coronaviruses (CoVs). The developed SARS-CoV-2 S1 subunit of the spike glycoprotein and nucleocapsid (N)-based ELISAs not only showed high specifcity and sensitivity but also did not show any cross-reactivity with other CoVs. We also show that all RT-PCR confrmed COVID-19 patients tested in our study developed both virus specifc IgM and IgG antibodies as early as week one after disease onset. Our data also suggest that the inclusion of both S1 and N in serological testing would capture as many potential SARS-CoV-2 positive cases as possible than using any of them alone. This is specifcally important for tracing contacts and cases and conducting large-scale epidemiological studies to understand the true extent of virus spread in populations.